Human Resources Planning Strategy with SWOT Analysis Method at PT. X (Largest Cigarette Distributor in Indonesia) - Ranthy Pancasasti; Dian Sapitri; Evan Nur Oktavian; Adi Mulyadi; Agung Aditya Saputra (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
This research aims to find out how the human resource planning strategy conducted by PT X Cigarette Distributor. This company is a cigarette distributor company and is the largest cigarette